2007
DOI: 10.5032/jae.2007.04082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Paradox Of Supervised Agricultural Experience Programs In Agricultural Education

Abstract: Agricultural teachers in North Carolina were surveyed to assess their attitudes toward Supervised Agricultural Experience (SAE) and to identify barriers to implementation of SAE in their schools. The teachers gave the politically correct answers about why SAE was important. The teachers indicated that SAE was important (8.46 on a 10 point scale) but confessed the quality of their SAE program was only a 6.33 on the 10-point scale. Furthermore, less than 1/3 of the teachers had a 75% or higher participation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 6 publications
3
41
1
Order By: Relevance
“…Novice (preservice) teachers are entering the profession having high self-efficacy toward their perceived abilities to develop, implement, communicate, maintain, sustain, evaluate, and supervise SAE; yet current teachers struggle with many aspects of SAE (Swortzel, 1996). Dyer and Osborne (1995), Retallick (2010), and Wilson and Moore (2007) all indicated that teachers do not implement SAE programs as they are conceptually and theoretically defined. Therefore, a gap between what is taught in pre-service programs and what is implemented in the classroom by practicing teachers exists.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Novice (preservice) teachers are entering the profession having high self-efficacy toward their perceived abilities to develop, implement, communicate, maintain, sustain, evaluate, and supervise SAE; yet current teachers struggle with many aspects of SAE (Swortzel, 1996). Dyer and Osborne (1995), Retallick (2010), and Wilson and Moore (2007) all indicated that teachers do not implement SAE programs as they are conceptually and theoretically defined. Therefore, a gap between what is taught in pre-service programs and what is implemented in the classroom by practicing teachers exists.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Since the mid-1980's, student participation and teacher usage of SAE programs has continued to decrease (Barrick, Hughes, & Baker, 1991;Dyer & Osborne, 1995;Phipps et al, 2008;Retallick, 2010;Roberts & Harlin, 2007;Steele, 1997;Wilson & Moore, 2007). Further, Steele (1997) conjectured that the removal of the federal legislative requirement has affected the utilization of supervised experiences within school-based agricultural education (SBAE) nationwide.…”
mentioning
confidence: 99%
See 3 more Smart Citations